ANALYSIS OF CRUISE SHIP TRAFFIC IN THE PORT OF SPLIT - Perić, Tina; Mihanović, Vice; Golub Medvešek, Ivana (Journal of Applied Engineering Science, 2019)
Cruise ship traffic is a part of a shipping industry, which is growing constantly both in number of ships and their capacity. Port of Split is second largest cruise port in the Croatia. Many analyses of cruise ship traffic were made for the city of Dubrovnik and some measures for improvement as a result have already been taken. The goal of this paper is to provide detailed analyses of cruise ship traffic in Port of Split as a basis for a future research of carrying capacity of Split’s cruise tourism in aspect of sustainable development.
Keywords: Port of Split; cruise traffic; cruise ship